2019
DOI: 10.1002/slct.201902542
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide (rGO)/ZrO2 Reinforced Polyimide Nanocomposite Aerogels with Enhanced Properties: A Synergistic Effect of the Nanofillers

Abstract: In this paper, linear-structured polyimide (PI) nanocomposite aerogels were fabricated with incorporation of graphene oxide (GO) and nano-sized zirconium dioxide (ZrO 2 ) via a freezedrying route. SEM images indicate GO and ZrO 2 dispersed well in PI network skeletons after imidization. GO and ZrO 2 can improve physical properties not only separately but also synergistically, generating excellent performances of the nano-composite aerogels with the density of 70 mg cm À 3 , porosity of 95%, shrinkage of 19% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Additionally, graphene's high specific surface area and two‐dimensional structure make it a useful material for load transferring 42 . Wu et al observed a similar type of effect when polyimide nanocomposites reinforced with rGO and Zirconia Oxide (ZrO 2 ) 53 . Graphene's high thermal conductivity and exceptional mechanical properties make it a prime candidate for tribology applications in polymer nanocomposites 54 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, graphene's high specific surface area and two‐dimensional structure make it a useful material for load transferring 42 . Wu et al observed a similar type of effect when polyimide nanocomposites reinforced with rGO and Zirconia Oxide (ZrO 2 ) 53 . Graphene's high thermal conductivity and exceptional mechanical properties make it a prime candidate for tribology applications in polymer nanocomposites 54 .…”
Section: Resultsmentioning
confidence: 97%
“…42 Wu et al observed a similar type of effect when polyimide nanocomposites reinforced with rGO and Zirconia Oxide (ZrO 2 ). 53 Graphene's high thermal conductivity and exceptional mechanical properties make it a prime candidate for tribology applications in polymer nanocomposites. 54 The sliding motion of the graphene interlayer also contributes to the increased wear resistance of the polymeric composites.…”
Section: Optical Microscopic Evaluation Of Wear Specimensmentioning
confidence: 99%